Old Elm speaks : tree poems - George, Kristine O'Connell.; Kiesler, Kate (New York : Clarion Books, 1998)
A collection of short, simple poems which present images relating to trees in various circumstances and throughout the seasons.
Wilson's Children.
School Library Journal starred.
Book Links (A.L.A.).
4.9
K-3
Center for the Collaborative Classroom Curriculum.
Keywords: Trees -- Juvenile poetry; Children's poetry, American; Trees -- Poetry; American poetry; Trees -- Poetry; Trees -- Poetry; Poetry -- Collections; American poetry